The Effect of the MAP Growth Test on Primary School Students’ Reading Comprehension: American Excellence Schools as a Case Study - Albataineh, Majde Mahmoud; Baniabdelrahman, Abdallah (Dirasat: Educational Sciences, 2023)
objectives: The purpose of this study is to investigate the effect of using the MAP Growth test in improving the reading comprehension of primary school students. The study uses American Excellence Schools in Jordan as a case study. Methods: The study sample included 30 male and female students who studied at American Excellence Schools which is a private school registered with the Directorate of Education of Amman. The study used a quasi-experimental design. The sample was divided into two experimental groups based on their performance in the MAP Growth pre-test assessment. A special instructional program was designed for each experimental group according to the directions in the user guide of the MAP Growth test so as to focus on the weaknesses and missing skills of each group, which were identified based on the results of the MAP Growth pre-test assessment. Upon the completion of the intstructional program, students took the MAP Growth post-test assessment, and data was analyzed to find whether there is any statistically significant differences at (α = 0.05) in the students’ mean scores in the reading comprehension post-test due to the use of the Map Growth test. Results: The results showed that there were statistically significant differences at the level (α = 0,05) in the total score of students’ reading comprehension for the two groups in favor of the post-test due to the use of the instructional program. Conclusions: The researchers recommend using the MAP growth test to enhance students’ reading comprehension skills.